Mexican american and immigrant poverty in the United States - Garcia, Ginny (The springer series on demographic methods and population analysis, 2011)
This book provides a comprehensive portrait of the experience of poverty among Mexican Americans and Mexican immigrants in the US. Given that these two groups experience some of the highest rates of poverty of any ethnicity and that it persists even while a majority work and reside in dual parent households, it becomes imperative that we explore a multitude of related factors. This book offers a systematic empirical analysis of these groups in relation to other ethnic groups, explores the individual and contextual factors associated with the determination of poverty via the use of logistic and multi-level models, details the historical context associated with Mexican immigrants, and discusses the major policies that have impacted them. It discusses the newest destinations of Mexican immigrants and also provides a discussion of undocumented migrants. Further, it details the current measure of poverty in the United States and offers a number of alternatives for modeling and measuring it. Acknowledgements -- Table of contents -- List of figures -- List of tables -- Nomenclature -- Chapter 1: Introduction -- Chapter 2: Prior studies -- Chapter 3: Settlement and geographic redistribution patterns -- Chapter 4: Data and methods -- Chapter 5: Individual level results: mexican americans -- Chapter 6: Individual level results: mexican immigrants -- Chapter 7: Multilevel analysis and results -- Chapter 8: Implications and policy suggestions -- Chapter 9: Conclusion -- References -- Index -- Appendix A -- Appendix B -- Appendix C.